Association of Rural Setting With Poorer Disease Outcomes for Patients With Rheumatic Diseases: Results From a Systematic Review of the Literature. Issue 5 (11th May 2021) - Hollick, Rosemary J.; Macfarlane, Gary J.
Abstract : Objective: To assess whether clinical and patient‐reported outcomes are poorer for individuals with inflammatory and noninflammatory rheumatic diseases living in rural locations. Methods: We searched 6 databases for articles that reported on primary peer‐reviewed research, published in English between 1990 and 2019, that focused on selected rheumatic diseases (rheumatoid arthritis [RA], psoriatic arthritis, axial spondyloarthritis, or osteoarthritis [OA]) and quantified either patient‐reported or clinically measured outcomes by a measure of rurality or remoteness. Selected articles were synthesized narratively. Results: Eight eligible publications, including 753 rural and 929 urban patients, evaluated outcomes in RA (5 studies) and OA (3 studies). Studies were small, single center, and rarely provided a definition of rurality. Aspects relating to rurality, such as access to services, were not measured. In RA, some studies suggested greater functional disability and disease activity in rural dwellers. In OA, there was some evidence to suggest that rural dwellers presented with more advanced degenerative hip changes, and that illness perceptions and coping differed between rural and urban dwellers. No studies examined work outcomes. Potentially important confounding factors such as socioeconomic status were rarely considered. Conclusion: There remains considerable uncertainty whether outcomes differ for patients with rheumatic disease in rural settings. There is a need for larger scale studies characterizing participants in relation to place of residence in order to determine whether rurality is an independent predictor of outcome or a surrogate marker for socioeconomic factors.